Effects of mindfulness-based stress reduction on cancer-related fatigue in patients with breast cancer: a meta-analysis of randomized controlled trials - Lan, XiaoQian; Xie, HongMei (Frontiers in Oncology, 2024)
IntroductionMindfulness-based stress reduction (MBSR) has been widely used for improving psychological symptoms and sleep quality in breast cancer patients and has a positive impact on posttraumatic growth and immunology. Moreover, MBSR is increasingly being used in cancer-related fatigue (CRF) intervention studies for breast cancer patients, but conflicting results also exist.ObjectiveThis study aimed to evaluate the effect of MBSR on CRF in patients with breast cancer.MethodsA comprehensive computer search of the Pubmed, Cochrane Library, Embase, Web of Science, China Biomedical Document Service System, China Knowledge Infrastructure Engineering, Wanfang Data Knowledge Service Platform, and VIP databases was performed. Randomized controlled trials (RCTs) published before April 10, 2023, were identified. The primary outcome was cancer-related fatigue associated with breast cancer. Two researchers independently screened the studies, extracted the data, and evaluated the methodological quality of the studies according to the inclusion and exclusion criteria. The Meta-analysis of the outcome indicators was performed using STATA 16.0 software.ResultsA total of 13 studies were included, including 1992 patients (997 patients in the MBSR group and 1015 patients in the control group). Compared with conventional care, MBSR significantly alleviated the symptoms of CRF in breast cancer patients (SMD=-0.32, 95% CI [-0.42, -0.22], z=6.54, p<.01). Under the supervision of experts, the 8-week MBSR had a great influence on CRF, especially in the Asian population.ConclusionsMBSR is effective in the treatment of CRF induced by breast cancer, and no obvious adverse effects occur; thus, MBSR can be recommended as a beneficial adjuvant therapy for treating CRF in breast cancer patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021245365.